2023
DOI: 10.1007/s42729-023-01233-3
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Applying Cobalt and Chitosan with Various Water Irrigation Schemes at Different Growth Stages of Corn on Macronutrient Uptake, Yield, and Water Use Efficiency

Abstract: While previous studies have demonstrated the positive effects of low cobalt (CB) levels and chitosan (CH) on yield and nutrient status, information about their individual and combined applications on plants under stress is still lacking. Therefore, we conducted a study to investigate CB and CH impacts on mitigating water stress during growth stages and their effects on corn macronutrient uptake and yield. Four irrigation schemes were employed, including (1) control (full irrigation), (2) 70% of irrigation wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…Additionally, this approach proves beneficial in mitigating the impacts of water stress and conserving significant amounts of irrigation water and increasing WUE in arid climatic conditions. These findings align with previous studies 14,59,67 , that have reported similar enhancements in yield characteristics.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Additionally, this approach proves beneficial in mitigating the impacts of water stress and conserving significant amounts of irrigation water and increasing WUE in arid climatic conditions. These findings align with previous studies 14,59,67 , that have reported similar enhancements in yield characteristics.…”
Section: Discussionsupporting
confidence: 93%
“…One of these mechanisms is the activation of an effective root system, which involves the penetration of the root system within the soil profile, the modification of root architecture as well as the accumulation of root exudate production, which is consistent with previous studies [56][57][58] . However, with reduced water applications (Ir 70 ), the soil pH increased subsequently affecting negatively on the availability of P 59 . The plants employ increasing root exudates to decrease soil pH and allow root systems increase the absorption of P. Increased accumulation of P in grains improves the synthesis of carbohydrates.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, under (100 & 80%) GWR levels, many stomata were open due to adequate soil moisture, resulting in increased transpiration rates 67 , 68 . This caused an imbalance in nutrient uptake activities between the most active plant aerial parts and roots, consistent with previous studies 5 , 23 . The current study’s findings suggest that under similar growth conditions (100 & 80%) GWR, applying foliar applications of Znfol to peanut plants has desirable effects.…”
Section: Discussionsupporting
confidence: 92%
“…Dang et al 73 also highlighted that plant growth and metabolism vary based on the concentration and state of Co in the rhizosphere and soil. Hence, previous studies 5 , 23 demonstrated that Co benefits are correlated with the irrigation level used. Hence, supplying stressful peanut plants with sole applications of Co proved to be a harmful technique, resulting in adverse impacts on yield and IWUE.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation